Exploring the use of portable mode A ultrasound for body composition assessment: A narrative review (Research, Society and Development, 2024)
The evaluation of body composition plays a crucial role in nutrition and is divided into direct, indirect, and doubly indirect techniques. The use of ultrasound (US) mode A, particularly with the BodyMetrix BX-2000 equipment, has become notable for its accessibility. However, there are still few studies that adequately describe its use. Therefore, this study aims to review the available literature on the validation of portable US mode A in different contexts and populations. When compared to other methods, the review reveals variations in accuracy, especially between men and women. Although the equipment appears to be valid for estimating body fat percentage, its accuracy varies in relation to reference methods, and the need for standardization is emphasized due to different measurement techniques and locations. In summary, the importance of further research for standardization in measurement procedures, including specific equations to estimate body composition with the obtained data, is emphasized.